Approaching the Downsizing Limit of Silicon for Surface‐Controlled Lithium Storage. (7th January 2015) - Wang, Bin; Li, Xianglong; Luo, Bin; Hao, Long; Zhou, Min; Zhang, Xinghao; Fan, Zhuangjun; Zhi, Linjie
<x xml:space="preserve">Abstract</x> Graphene‐sheet‐supported uniform ultrasmall (≈3 nm) silicon quantum dots have been successfully synthesized by a simple and effective self‐assembly strategy, exhibiting unprecedented fast, surface‐controlled lithium‐storage behavior and outstanding lithium‐storage properties including extraordinary rate capability and remarkable cycling stability, attributable to the intrinsic role of approaching the downsizing limit of silicon. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>